Homogeneous Photocatalytic Degradation of Acid Alizarin Black Using Hydrogen Peroxide - Mohammad Salim, Haydar A.; Mohammad Salih, Sabir A.; Simo, Sherwan M. (Science Journal of University of Zakho, 2014)
Photocatalytic degradation of acid alizarin black (AAB) dye (C.I. 21725) in aqueous solution was investigated using UV light in the presence of hydrogen peroxide (H2O2) as a catalyst at different operating conditions. The operating conditions were concentration of catalyst dosage (0.1, 0.2 and 0.3 mL of 30 % H2O2), initial concentration of AAB dye (100, 150 and 200 mg/L) and pH (3.3, 6.84 and 10.8). It was found that the increasing of catalyst concentration enhanced the dye decolourisation. Hydrogen peroxide exerted positive effects on the AAB removal whilst the initial concentration of AAB negatively affected its removal. It was also found that the removal efficiency of AAB increased with the pH value close to neutral (pH 7), while a reversed trend was observed at acidic and basic medium.